2004
DOI: 10.1021/jf035203w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irradiated Phytic Acid on Antioxidation and Color Stability in Meat Models

Abstract: Lipid oxidation and color stability of meats treated with irradiated phytic acid were investigated during storage for 2 weeks at 4 degrees C. The phytic acid in deionized distilled water (DDW) was degraded by irradiation at 10 and 20 kGy, and the irradiated phytic acid showed a strong antiradical activity. For measuring the antioxidant effects of irradiated phytic acid in food models, beef and pork were prepared with DDW (control), irradiated (10 and 20 kGy) or non-irradiated phytic acid, and ascorbic acid as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…PA in the above concentration range did not scavenge DPPH radical ( P > 0.05). These results are in agreement with earlier findings, where the scavenging effect of PA was observed after its irradiation only and it was positively correlated with irradiation dose [20, 21]. Ahn et al [22] conducted a similar study to evaluate antioxidant activities of irradiated PA and ascorbic acid.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…PA in the above concentration range did not scavenge DPPH radical ( P > 0.05). These results are in agreement with earlier findings, where the scavenging effect of PA was observed after its irradiation only and it was positively correlated with irradiation dose [20, 21]. Ahn et al [22] conducted a similar study to evaluate antioxidant activities of irradiated PA and ascorbic acid.…”
Section: Resultssupporting
confidence: 91%
“…It is known that PA can effectively and dose-dependently inhibit lipid peroxidation in beef and pork homogenates [28, 29]. Park et al [21] concluded that irradiated PA significantly inhibited lipid oxidation in meat homogenates compared to the control sample. Moreover, it was shown that irradiated PA was capable of preventing the loss of the heme iron and myoglobin formation during meat storage.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, IP 6 contains six phosphates, as shown in Figure 1B, and has a strong chelating action, binding minerals such as calcium, iron, and zinc and causing a decrease in their bioavailability in human and animal models. However, a recent study reported that phytic acid has a wide range of beneficial effects including antioxidant, anticarcinogenic, hypoglycemic, and hypolipidemic properties (13). IP 6 is considered to be an antioxidant agent as it is a potent inhibitor of iron-catalyzed hydroxyl radical formation by chelating free iron and then blocking its coordination site (14).…”
Section: Introductionmentioning
confidence: 99%
“…For each sample, a * value increased at early stage then decreased until the end of storage. The decrease in a * value has frequently been associated with the formation of metmyoglobin which results in discoloration of meat (Jeremiah ; Park and others ).…”
Section: Resultsmentioning
confidence: 99%